2022
DOI: 10.3390/bs12070244
|View full text |Cite
|
Sign up to set email alerts
|

A Rasch Analysis of Students’ Academic Motivation toward Mathematics in an Adaptive Learning System

Abstract: Despite the criticality of considering student academic motivation as it influences learning, research within the field of adaptive learning technologies for education has so far focused more on customising instruction to implement personalised learning, than investigating how personalised learning is associated with learners’ motivation. Given this, a robust instrument is required to gather information about student academic motivation within the context of adaptive learning technologies. This study sought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…House and Telese [42] indicated that there is a significant positive relationship between student engagement and academic achievement. Students' engagement could be promoted through collaborative learning, as this has a positive impact on student learning behaviors and academic achievement [43]. Teamwork engagement has a positive influence on students' personal success, learning and work satisfaction [44].…”
Section: Student Factorsmentioning
confidence: 99%
“…House and Telese [42] indicated that there is a significant positive relationship between student engagement and academic achievement. Students' engagement could be promoted through collaborative learning, as this has a positive impact on student learning behaviors and academic achievement [43]. Teamwork engagement has a positive influence on students' personal success, learning and work satisfaction [44].…”
Section: Student Factorsmentioning
confidence: 99%
“…[ 12 ], researchers have further added that satisfaction and self-efficacy lead to user intentions of utilising learning systems [ 13 , 14 ]. Even though it is crucial to account for user satisfaction as it affects learning, research in the area of adaptive learning technologies for education has concentrated more on tailoring instruction to implement personalised learning, rather than exploring how personalised learning is related to learner satisfaction [ 15 ]. Further, multiple published instruments assessing learner satisfaction have been developed within the context of instructor-led courses, as opposed to student-centred, self-led adaptive learning courses.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 , 24 ] concurred with similar viewpoints by postulating that user satisfaction is one of the most important factors when addressing the success of an information system. Nonetheless, this has not been thoroughly evident within research of adaptive learning technologies for education, with more focussing on methods to personalise learning [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical classes aim to develop the education seekers' logical thinking, provide a basis for acquiring scientific activity skills. At the same time, the implementation of personal qualities and acquisition of the abilities mentioned above by pupils and students requires intense and systematic independent work (Lim et al, 2022).…”
Section: Literature: 1 Introductionmentioning
confidence: 99%